2009
DOI: 10.1007/s12272-009-1320-0
|View full text |Cite
|
Sign up to set email alerts
|

Two enone fatty acids isolated from Gracilaria verrucosa suppress the production of inflammatory mediators by down-regulating NF-κB and STAT1 activity in lipopolysaccharide-stimulated RAW 264.7 cells

Abstract: Gracilaria verrucosa is a common marine red alga that has anti-oxidant and anti-cancer properties. Recently, we reported that anti-inflammatory constituents of G. verrucosa operate through an unknown mechanism. For this reason, we isolated two enone fatty acids from G. verrucosa and investigated their molecular mechanism in LPS-stimulated RAW264.7 cells. We found that the two compounds inhibited the production of inflammatory markers (nitric oxide, TNF-alpha, and IL-6) in a dose-dependent manner. We next studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 41 publications
2
20
1
Order By: Relevance
“…The enone fatty acid analogues, including C10, not only downregulated the expression of inducible nitric oxide synthase (iNOS), TNF-· and IL-6 in LPS-stimulated macrophages, but also blocked various inflammation-and apoptosis-related signaling pathways, such as the Janus kinase (Jak)/signal transducer and activator of transcription 1 (Stat1) and NF-κB pathways. In contrast, these compounds did not inhibit PI3K/mitogen-activated protein (MAP) signaling (35). In the present study, we show that C10 inhibits ERK, JNK and NF-κB signaling in macrophages stimulated by LPS.…”
Section: Discussioncontrasting
confidence: 59%
“…The enone fatty acid analogues, including C10, not only downregulated the expression of inducible nitric oxide synthase (iNOS), TNF-· and IL-6 in LPS-stimulated macrophages, but also blocked various inflammation-and apoptosis-related signaling pathways, such as the Janus kinase (Jak)/signal transducer and activator of transcription 1 (Stat1) and NF-κB pathways. In contrast, these compounds did not inhibit PI3K/mitogen-activated protein (MAP) signaling (35). In the present study, we show that C10 inhibits ERK, JNK and NF-κB signaling in macrophages stimulated by LPS.…”
Section: Discussioncontrasting
confidence: 59%
“…Algae found growing in abundance off the coastal areas of many parts of the world represent a huge yet untapped potential for new source of therapeutics [12,13]. The red algae for example has been reported to contain active compounds that may help ameliorate inflammation of the alimentary tract [14], prevent or treat gastric ulcers and cancers caused by oxidative stress [15,16], inhibit inflammatory activities by suppressing the production of inflammatory mediators [17-19] and induce cancer cell apoptosis in stomach [20] and colon [21]. Natural compounds derived from the edible algae could be safer to be used as anti-inflammatory and gastric anti-ulcerogenic therapeutics as they have been taken as food and used in traditional medicines since time immemorial [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that some constituents of Gracilaria possess anti-inflammatory properties [23], [33], [34]. COX-2, a pro-inflammatory enzyme, is linked to HCV-associated liver carcinogenesis [10].…”
Section: Resultsmentioning
confidence: 99%